Beyond hunger: Monitoring food insecurity in the SDG era - Cafiero, Carlo (2018)
Carlo Cafiero IFPRI-FAO conference, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand